2021
DOI: 10.1186/s40850-021-00083-9
|View full text |Cite
|
Sign up to set email alerts
|

The dark-ventral-patch of male red deer, a sexual signal that conveys the degree of involvement in rutting behavior

Abstract: Background In polygynous mammals, signalling may play a decisive role in mating behavior, mediating the intensity of male fights and female mate choice. During the rutting season, male red deer may show a visible dark patch in their ventral fur. Recently, this patch has been suggested to act as a flexible sexual signal, due to its relationships with other variables such as age, body size, antler development, volatile compounds, or the competitive environment. The analysis of fur pigmentation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…We observed that blink rate in both species decreased as group size increased. The data for this study was collected between February and May, and as a result, individuals could be displaying residual stress and therefore heightened vigilance as a result of the intense male interactions that occur during the rut [30,39,40], further seen with the reduced rate seen in male red deer. In mixed-sex groups, similar to the group observed in this study, vigilance was observed to not decrease as group size increased in Pere David's deer Elaphurus davidianus [40], which the authors attributed to the threatening nature of males during the rut.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that blink rate in both species decreased as group size increased. The data for this study was collected between February and May, and as a result, individuals could be displaying residual stress and therefore heightened vigilance as a result of the intense male interactions that occur during the rut [30,39,40], further seen with the reduced rate seen in male red deer. In mixed-sex groups, similar to the group observed in this study, vigilance was observed to not decrease as group size increased in Pere David's deer Elaphurus davidianus [40], which the authors attributed to the threatening nature of males during the rut.…”
Section: Discussionmentioning
confidence: 99%
“…Javan deer also performed minor seasonal behaviours, for example, rutting. Rutting or mating behaviour would be fighting among adult males (Powell & Evans 2019;de la Peña et al 2021).…”
Section: Daily Behaviour Patterns Of Javan Deermentioning
confidence: 99%
“…The dark ventral patch is a quality signal that conveys information about the mating effort during the rut [19,22]. Males with larger patches are more involved in the rut and achieve higher mating success than males with small patches [21]. Unlike antlers, which are produced several months before the starting of the rutting season, the ventral patch may be more modulable in the short term [22].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism suggested here for a exible trait development and associated behavioral display [21] represents a rare example of adaptive regulation based on gene expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation